The Role of Non-Technical Skills in the Software Development Market - Rabelo, Dannilo; Lopes, Albert; Mendes, Wendy; Souza, Cleidson de; Gama, Kiev; Monteiro, Danilo; Pinto, Gustavo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Software development is an intrinsic collaborative profession, which demands a rich set of technical and non-technical skills. In particular, the recent changes that shifted the software development practice (from a collaborative in-person based activity to an intrinsic geographically distributed one) accelerated the need of non-technical skills. In this work, we aimed to draw the current landscape of non-technical skills in the software development area. To achieve this goal, we conducted a two-phase study. We started by inspecting 566 job post advertisement to assess how often these skills are requested. In the second phase, we interviewed 15 junior developers to find out which non-technical skills they think are required in their organizations, and to understand how they exercise these non-technical skills. Our results suggest that 98,9% of the job posts mentioned at least one non-technical skill, averaging 6.30 non-technical skills per job post. Our interviewees believe that non-technical skills help them to understand the organizational culture, the team dynamics, and their careers. In summary, we believe that our work contributes to pile additional evidence on the need that software professionals have in mastering these non-technical skills.